2019
DOI: 10.21787/jbp.11.2019.125-136
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Utilization of the 2018 Village Funds in Bintan District and Lingga District

Abstract: The Village funds are part of the State Revenue and Expenditure Budget which are allocated for villages and disbursed through the district/city expenditure budget. During the period of 2015-2018, two village heads (village of Malang Rapat and Penaga) were the suspects of corruption cases in Bintan District in the province of Riau Islands. There was no evaluation of the use of the village funds by the district government. The objective of this study was to gain an insight into the use of village funds in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, the village fund has been mostly spent on infrastructure development (Sutiyono et al, 2018). Research conducted in Bintan District and Lingga District found that most village funds are used for physical development (Adhayanto et al, 2019). Using Village Fund considerably to build infrastructure will only have a little impact on poverty alleviation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the village fund has been mostly spent on infrastructure development (Sutiyono et al, 2018). Research conducted in Bintan District and Lingga District found that most village funds are used for physical development (Adhayanto et al, 2019). Using Village Fund considerably to build infrastructure will only have a little impact on poverty alleviation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the government's efforts to boost rural development is through the implementation of village fund transfer since 2015. Village funds can be allocated by the village government to build small-scale infrastructure facilities and to strengthen the capacity of the local community by providing some empowerment programs (Adhayanto et al, 2019;Arifin et al, 2020). Several studies have concluded that village fund transfers can reduce poverty levels in villages (Arham & Hatu, 2020;Saragi et al, 2021;Andi Setiawan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most crucial tasks is found in point a, which reads: "(a) determining the boundaries of the Nagari territories following cartographic principles.". The government did the correction of policy, the test of surveillance model, a workshop for the head of villages and staff, and run the mobilization of experienced village companions (Adhayanto et al, 2019).…”
Section: Methodsmentioning
confidence: 99%